Efforts to Reduce Pollution in the Denai River - Sinaga, Agnes; Pandiangan, Errason; Sinurat, Ester; Anggi, Ika; Rahmat, Riki; Yuniastuty, Eni (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
River pollution is a serious problem that occurs due to the entry of hazardous substances into river water, thus reducing water quality and disrupting the function of its ecosystem. The main causes of river pollution include indiscriminate waste disposal, industrial waste containing hazardous chemicals, household waste, and unsustainable agricultural activities. This condition causes various negative impacts, such as the emergence of water-related diseases, threats to biodiversity, depletion of clean water supplies, and eutrophication that can kill aquatic organisms. This study aims to determine efforts that can be made to reduce or prevent pollution of the Denai River, by considering the condition of existing water resources. The study was conducted through observation, interviews, and documentation studies. The results of the study indicate that river management is carried out by the governor, for rivers in river areas across districts / cities, in river management is carried out by involving technical agencies and related community elements based on norms, standards, guidelines, and criteria set by the Minister. River management includes river conservation; river development; and control of the destructive power of river water, carried out through the stages of preparing programs and activities; implementing activities; and monitoring and evaluation. River conservation is carried out through river protection activities and preventing river water pollution.